DAUR TEBANG OPTIMAL HUTAN RAKYAT GMELINA (Gmelina arborea Roxb.) DI TASIKMALAYA DAN BANJAR, JAWA BARAT, INDONESIA - Yonky Indrajaya; M Siarudin (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2015)
Determination of cutting cycle on plantation forest including private forest, is an important step to gain maximum profit in the plantation forest management. This study aims to analyze optimal harvesting rotation of gmelina private forest in Tasikmalaya and Banjar, West Java. The method used was profit maximization obtained from all rotation of gmelina stand. Data collected were stand growth and economic data. Stand growth was collected through field measurement and through interview with gmelina farmer for economic data. The results of this study are: a) optimal biological rotation of gmelina stand is 8 years; b) Faustmann rotation of gmelina stand is 10.5 years; c) the length of Faustmann rotation is negatively correlated with stumpage price, interest rate and wood production reduction, but positively correlated with planting cost.